Clinical outcome in patients with cardiovascular diseases with COVID-19 in the second macro-region of Alagoas - Santos, Carlos Rodrigo dos; Santos, Paula Dayane Silva; Silva, Danielle Alice Vieira da; Mota, Luciana de Melo; Silver, Thays Fernanda Costa; Lisbôa, Gabrielle Leite Pacheco (Revista Prevenção de Infecção e Saúde, 2023)
Introduction: Body's response to the COVID-19 virus leads to systemic inflammation, in which there is an increase in inflammatory markers and myocardial injury and/or cardiac dysfunction, predisposing the individual to acute heart failure, myocarditis, thrombosis and arrhythmias. Aim: to describe the main clinical outcomes of individuals with COVID-19 who reported cardiovascular problems. Outlining: this is a documentary study with quantitative approach. The research is based on the hospital censuses issued to the municipal health department of Arapiraca. The research has included the individuals infected with COVID-19 who self-reported preexistent cardiovascular diseases upon hospital admission, excluding the ones who developed cardiovascular diseases during hospitalization. Thus, the data analyzed were comprehended in the July to December 2020 period. The study was carried out between August and September 2021. After collecting the information, basic descriptive statistics were performed to systematize the data. Results: among the 260 self-reported cases of cardiovascular disorders, systemic arterial hypertension stands out for registering 85.38% of the cases. Next, cardiopathies exhibit 24.62% of occurrences. That said, it was possible to observe that the highest death rate was presented by heart diseases with 31.58% of the cases. On the other hand, it is noted that the highest rate of discharge occurrences was in patients with systemic arterial hypertension, with 55.40% of the target audience. Implications: the investigation made it possible to verify that discharge due to cure and death were the main clinical outcomes, respectively.